The Effect of the Accor Live Limitless (ALL) Loyalty Program on Repurchase Intention Mediated by Guest Satisfaction at Peppers Seminyak Bali - Valentino Yuda Agustin; Hijriyantomi Suyuthie (Journal of Multidimensional Management, 2025)
This study investigates the direct and indirect effects of the Accor Live Limitless (ALL) loyalty program on repurchase intention at Peppers Seminyak Bali, Indonesia, with guest satisfaction as a mediating variable. A quantitative research design with an associative–causal approach was employed, involving 100 respondents who were ALL members and had stayed at the hotel within the past year, selected using the Slovin formula (10% margin of error) and simple random sampling. Data were collected through validated self-administered questionnaires on a five-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 4.0. Results revealed that the loyalty program had a positive and significant effect on both repurchase intention (β = 0.239, t = 2.923, p = 0.003) and guest satisfaction (β = 0.373, t = 3.631, p < 0.001). Guest satisfaction also exhibited a strong and significant influence on repurchase intention (β = 0.574, t = 6.513, p < 0.001) and partially mediated the loyalty program–repurchase intention relationship (β = 0.214, t = 2.987, p = 0.003). Theoretically, this research extends loyalty and satisfaction models in luxury hospitality, while practically, it offers insights for hotel managers to optimize loyalty program benefits through personalized rewards, streamlined redemption processes, and consistent service excellence to strengthen guest retention.